2009
DOI: 10.1073/pnas.0812097106
|View full text |Cite
|
Sign up to set email alerts
|

Impaired recollection but spared familiarity in patients with extended hippocampal system damage revealed by 3 convergent methods

Abstract: To understand recognition memory, the detection of stimulus repetition, it first is necessary to resolve the debate between 2 fundamentally different models of recognition. Contemporary single-process models assume that recognition memory relies solely on the neural system required for the recall of prior events. Dual-process models assume that recognition comprises 2 independent forms of memory: one supports recall, and the other detects repeated stimuli by signaling their familiarity, the feeling of previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
151
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 31 publications
12
151
1
Order By: Relevance
“…Previous reports using the D&P test had already indicated a selective effect of hippocampal damage on recall (7)(8)(9)(19)(20)(21)(22), but those studies did not examine whether this selective mnemonic effect was correlated with extent of hippocampal damage. Because our patient cohort was a large one and had wide variation in extent of hippocampal atrophy, we were able to examine this structure/function relationship and found a sharp distinction between recall and recognition performance, with only the former showing a correlation with extent of HV loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports using the D&P test had already indicated a selective effect of hippocampal damage on recall (7)(8)(9)(19)(20)(21)(22), but those studies did not examine whether this selective mnemonic effect was correlated with extent of hippocampal damage. Because our patient cohort was a large one and had wide variation in extent of hippocampal atrophy, we were able to examine this structure/function relationship and found a sharp distinction between recall and recognition performance, with only the former showing a correlation with extent of HV loss.…”
Section: Discussionmentioning
confidence: 99%
“…6). Also, studies examining the effects of damage to the mammillary bodies and fornices, structures within the hippocampal circuit, have shown that volume loss is correlated with deficits in recall but not in recognition (7,8).However, there is also evidence suggesting that both processes rely on the hippocampus (for a review, see ref. 6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As focal damage to the fornix and mammillary bodies results in impaired performance that resembles that of hippocampal damage (Dusoir et al 1990;Tsivilis et al 2008;Rudebeck et al 2009;Vann et al 2009b), it has been suggested the study of hippocampusbased memory should be extended to include the fornix and mammillary bodies as part of the "extended hippocampal system" (Aggleton and Brown 1999).…”
Section: Hippocampus and Mtlmentioning
confidence: 99%
“…5 To assess episodic memory in more detail in MCI, it was important to select measures that minimized the risk of patients performing at floor level. The visual recognition test from the Doors and People Test 23 and the face recognition test from the Camden Recognition Memory Test (CRMT) 24 have proven utility in amnestic patients 25 and were therefore chosen. Recollection-vs familiarity-based recognition processes were probed further in the CRMT with the "rememberknow" procedure.…”
mentioning
confidence: 99%